2021
DOI: 10.15537/smj.2021.42.10.20210504
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interspace between the popliteal artery and the capsule of the posterior knee (iPACK) block versus periarticular local infiltration analgesia after unilateral total knee arthroplasty

Abstract: To compare the efficacy of interspace between the popliteal artery and the capsule of the posterior knee (iPACK) block with periarticular local infiltration analgesia (LIA) to assess postoperative pain control and enhanced recovery after total knee arthroplasty (TKA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A total of 17 publications with 1652 patients were included [ 1 , 9 , 15 17 , 19 , 20 , 22 , 23 , 27 , 28 , 31 33 , 35 , 37 , 41 , 43 ], consisting of 16 RCTs and one prospective control trial. The trial characteristics are represented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 17 publications with 1652 patients were included [ 1 , 9 , 15 17 , 19 , 20 , 22 , 23 , 27 , 28 , 31 33 , 35 , 37 , 41 , 43 ], consisting of 16 RCTs and one prospective control trial. The trial characteristics are represented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Data from 11 studies ( n = 901) described the LOS, and 10 studies ( n = 747) described patient satisfaction after TKA with IPACK supplementation, respectively [ 9 , 16 , 17 , 19 , 20 , 22 , 23 , 28 , 31 , 33 , 41 , 43 ]. The research strongly confirmed that it could shorten LOS (95% CI − 0.40 [− 0.64, − 0.15], I 2 = 70%, p = 0.001) and improve patient satisfaction (95% CI 0.43 [0.01, 0.84], I 2 = 87%, p = 0.04) (Figs.…”
Section: Resultsmentioning
confidence: 99%